基于直接法与图示理论形态对《国际汉语教学案例分析与点评》教材的分析与总结 - DAVID VINCENSIUS (Journal International Lingua Mandarin (JILIN), 2023)
在国际汉语教学中，不同的教学对象、教学内容可以采取不同的教学理论和教学方法，但是其最终目的是培养学习者的语言运用能力和言语交际能力。使用文献研究法，本文基于直接法和图式理论的角度形态，以国际中文教育专业研究生教材《国际汉语教学案例分析与点评》（主编叶军）中的国际汉语教学案例为例来分析直接法与图式理论在国际汉语教学中的应用效果，让国际汉语教师或者志愿者可以从中吸取教训，积累经验。In international Chinese language teaching, the diverse teaching theories and methods can be adopted according to different teaching objects and contents needed, but the ultimate goal is to cultivate learners' ability in language usage and verbal communication. Using the literature research method, this paper is based on the perspectives of direct method and schema theory, taking the international Chinese teaching cases in the international Chinese language teaching postgraduate textbook Case Analysis and Comment on International Chinese Teaching (Editor-in-Chief Ye Jun) as examples to analyze the application effect of direct method and schema theory in international Chinese teaching. So the International Chinese language teachers or volunteers can learn lessons and accumulate experiences.